Determination of Eco-Efficiency in Food Waste Generated at the Household Level: Pilot Case in Chile - Cáceres, Paola (2021)
[Introduction]: The home is the link in the food chain that contributes the most to food waste in the world. In Chile, there are no data on the quantity and/or composition of the waste generated at the household level, and its environmental impact is unknown. [Objectives]: Determine eco-efficiency as an indicator of the environmental impact of food waste, based on the calculation of its water footprint (HH), caloric intake, and economic cost. [Methodology]: A descriptive pilot study of 15 middle/lower-middle socioeconomic level households in Santiago, Chile; it was conducted based on waste obtained by daily recording and weighing. The wastes were classified into vegetable and animal types according to their origin; their water footprint, caloric intake, and economic cost were determined. The data collected was used to calculate eco-efficiency (EE) according to three different equations. [Results]: The total waste generated was 54.7 kg in one week, with vegetable products responsible for 80.9 % of the total. The caloric value was 65,028 kcal (1,141 kcal per person), while the economic cost reached CLP 83,444 (USD 102.02). The HH was 112 136.66, with animal products responsible for 67.8 % of the total. In EE calculations, the worst results were related to the amount of waste of animal origin. [Conclusions]: Knowing the environmental impact of food waste at the household level in Chile is a fundamental step for developing public policies or educational campaigns to promote sustainable consumption.